2016
DOI: 10.1021/acs.inorgchem.5b02327
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Interactions of the Cyanobacterial Metallothionein SmtA with Uranium

Abstract: Molecules for remediating or recovering uranium from contaminated environmental resources are of high current interest, with protein-based ligands coming into focus recently. Metallothioneins either bind or redox-silence a range of heavy metals, conferring protection against metal stress in many organisms. Here, we report that the cyanobacterial metallothionein SmtA competes with carbonate for uranyl binding, leading to formation of heterometallic (UO2)(n)Zn4SmtA species, without thiol oxidation, zinc loss, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Similarly, UO2 2+ may bind to these metalloproteins, depending on the properties of their surfaces, and cause structural and functional consequences. Acharya and Blindauer reported that UO2 2+ can bind to the cyanobacterial metallothionein SmtA, and form a heterometallic (UO2 2+ )nZn4SmtA species, without alteration of the native Zn4Cys9His2 cluster [49]. 1 H-NMR and molecular modeling studies In addition to a single metal ion or metal cofactor, metalloproteins may harbor multiple metal ions forming metal clusters that play either structural roles, electron-transfer, or catalysis functions [47].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, UO2 2+ may bind to these metalloproteins, depending on the properties of their surfaces, and cause structural and functional consequences. Acharya and Blindauer reported that UO2 2+ can bind to the cyanobacterial metallothionein SmtA, and form a heterometallic (UO2 2+ )nZn4SmtA species, without alteration of the native Zn4Cys9His2 cluster [49]. 1 H-NMR and molecular modeling studies In addition to a single metal ion or metal cofactor, metalloproteins may harbor multiple metal ions forming metal clusters that play either structural roles, electron-transfer, or catalysis functions [47].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Thirdly, although some structural features of uranyl-protein complexes are well-documented [7][8][9], it is still needed to obtain more structural information for uranyl-protein complexes, not only in solid state (such as X-ray crystal structure [10]), but also in solution state (such as NMR structure [49]), for a deep understanding of uranyl-induced conformational changes.…”
Section: Fetuin-a 3 Binding Sites~30 Nm-10 µMmentioning
confidence: 99%
“…The lack of a rigid structure allows MTs to coordinate a number of metals including essential metals like zinc and copper [11], toxic metals like cadmium [12] and mercury [13], and exotic metals like uranium [14] and technetium [15]. This flexibility, while fundamental to their function, makes MTs extremely difficult to characterize structurally.…”
Section: Metallothioneinmentioning
confidence: 99%
“…Cadmium supplementation has also been shown to produce MT dimers isolated from rabbit liver . Significant amounts of dimerization has been reported for the interaction of bacterial MT with uranyl salts (UO 2 2+ ) where the stable dimer product was subsequently characterized by proteolytic digestion and analysis by Ellman's method using 5,5′‐dithiobis(2‐nitrobenzoic acid) to quantify free thiols . The bacterial MT was completely oxidized and formed significant numbers of ions in the ESI‐MS spectrum, some of which overlapped with the monomer .…”
Section: Introductionmentioning
confidence: 99%
“…Significant amounts of dimerization has been reported for the interaction of bacterial MT with uranyl salts (UO 2 2+ ) where the stable dimer product was subsequently characterized by proteolytic digestion and analysis by Ellman's method using 5,5′‐dithiobis(2‐nitrobenzoic acid) to quantify free thiols . The bacterial MT was completely oxidized and formed significant numbers of ions in the ESI‐MS spectrum, some of which overlapped with the monomer . This overlap is crucial, as it may confound one of the few techniques available for structural analysis of the dynamic and difficult to characterize MT.…”
Section: Introductionmentioning
confidence: 99%